Technological valuation Management in plastic packaging companies in Bogotá, Colombia - Jiménez Hernández, Claudia N.; García Vergara, María E.; Castellanos Domínguez, Oscar F. (Cuadernos de Administración, 2017)
Technology Valuation is an ongoing topic, related to the estimation of a technological asset value usually within the framework of Technology Transfer activities. Its research and application occur mainly in industrialized countries; the most documented experiences come from these countries, meanwhile the contrary occurs in developing countries. The objective of this paper is to analyze the Management of Technology Valuation in several companies located at Bogotá (Colombia) and to identify challenges in this topic for these organizations. For this purpose, some companies from Bogotá city were studied, using benchmarking techniques. The results show the poor management and application of this valuation in the consulted companies, which agrees with the literature regarding the technological valuation in this context. Therefore, the challenges in the Management of Technology Valuation for the analyzed companies are oriented to the appropriation of valuation concepts and methods, as well as the strengthening and measurement of technological capabilities.